Role of Osteopontin in Spinal Pathologies - a systematic review - Junjie Lin (2021)
Worldwide, spinal diseases are an increasingly prevalent health problem. Deeper knowledge about the pathophysiology of this complex group of diseases could improve current prevention strategies and treatment options. Osteopontin (OPN) is a multifunctional protein with great interest among the scientific community as it possesses diversified functions which can be therapeutically targeted. In this research we appraised the role of osteopontin and its expression in different spinal pathologies. Thus, a systematic literature review search for published studies concerning the role of osteopontin in spinal pathologies was conducted. An interesting correlation between the expression of OPN and the presence or clinical severity of 8 different spinal pathologies of diverse etiologies was found and analyzed in this review, demonstrating the involvement of this molecule in these diseases. Its levels correlated with the course and outcome in theses diseases. OPN appears to have a broad spectrum of functions in spinal pathologies, including inflammatory and immune response, neural response to injury, abnormal tissue mineralization, osteogenic differentiation, bone metabolism, organ fibrosis and wound healing. Therefore, in the future, OPN might be a potential target for development of novel therapies or work as a prognostic tool in the onset and progression of spinal diseases.